Heterogeneous Origin of Gonadotropin Releasing Hormone-1 Neurons in Mouse Embryos Detected by Islet-1/2 Expression - Shan, Yufei; Saadi, Hassan; Wray, Susan (Frontiers in Cell and Developmental Biology, 2020)
In vertebrates, Gonadotropin releasing hormone-1 (GnRH) neuroendocrine cells originate in the olfactory placode and migrate into the forebrain where they regulate reproduction. However, the embryonic lineage of their progenitors remains controversial. Most GnRH neurons are derived from placodal ectodermal progenitor cells, but data from lineage tracing in zebrafish (Whitlock et al., 2003) and mouse (Forni and Wray, 2012) indicate that some GnRH progenitor cells have a neural crest origin. In contrast, a recent study in zebrafish (Aguillon et al., 2018), using Islet-1/2 expression, identified this LIM-homeodomain protein in all developing GnRH neuroendocrine cells, and the authors concluded a homogenous origin from progenitors within the preplacodal ectoderm. Evidence in different animal models and systems suggests that expression of Islet-1 plays a pivotal role in cell fate specification and differentiation. Thus, expression of Islet-1/2 in all GnRH cells in the nasal placode may not be lineage dependent but rather initiated locally in the placode as part of the program for GnRH cell specification and/or differentiation. This study addresses this issue and shows two populations of olfactory derived GnRH neurons in embryonic mouse: Islet-1/2(+) and Islet-1/2(-). Notably, triple-label immunofluorescence using the neural crest lineage tracer Wnt1, showed that GnRH neurons derived from Wnt1 progenitors are Islet-1/2(-). These results are consistent with two separate origins of GnRH neuroendocrine cells and suggest that either 1) NC-derived GnRH cells differentiate earlier than PE-derived GnRH cells or 2) different programs are used for cell specification in NC- vs PE-derived GnRH cells.